2010
DOI: 10.1182/blood-2010-02-271692
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up and factors influencing outcomes after related HLA-identical cord blood transplantation for patients with malignancies: an analysis on behalf of Eurocord-EBMT

Abstract: We analyzed risk factors influencing outcomes after related (R) human leukocyte antigen-identical cord blood transplantation (CBT) for 147 patients with malignancies reported to Eurocord-European Group for Blood and Marrow Transplantation. CBT has been performed since 1990; median follow-up was 6.7 years. Median patient age was 5 years. Acute leukemia was the most frequent diagnosis (74%). At CBT, 40 patients had early, 70 intermediate, and 37 advanced disease. CB grafts contained a median of 4.1 ؋ 10 7 /kg to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…16,17,28 The previously reported advantages of CBT include a lower incidence and severity of GVHD, ease of hematopoietic stem cell procurement, negligible risk of transmission of viral infections, and no donor risk/attrition. 15,29 In this analysis, we found that the incidence of grade II-IV acute GVHD was lower in our patients transplanted with CB cells than in those receiving BMT, which confirmed previous observations, 16,28 and that grade IV acute GVHD was not recorded after CBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,28 The previously reported advantages of CBT include a lower incidence and severity of GVHD, ease of hematopoietic stem cell procurement, negligible risk of transmission of viral infections, and no donor risk/attrition. 15,29 In this analysis, we found that the incidence of grade II-IV acute GVHD was lower in our patients transplanted with CB cells than in those receiving BMT, which confirmed previous observations, 16,28 and that grade IV acute GVHD was not recorded after CBT.…”
Section: Discussionmentioning
confidence: 99%
“…10,[12][13][14] In the last two decades, cord blood (CB) from an HLA-identical sibling increasingly is being used as an alternative source of hematopoietic cells for transplanting patients with either malignant or nonmalignant hematological diseases. [15][16][17] In particular, HLAidentical sibling CB transplantation (CBT) is associated with a low incidence of both acute and chronic graft-versus-host disease (GVHD), leading to a lower risk of fatal or life-threatening immune-mediated complications. 16 After anecdotal reports of successful CBT in children with TM or SCD, [18][19][20] a study from the Eurocord cooperative group, analyzing the outcome in 44 patients who had SCD or TM and were treated by CBT from a sibling donor, reported no fatal transplantation-related complications, suggesting that related CBT is a safe treatment for hemoglobin disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting experience with unrelated UCB transplantation (UCBT), modifications of conditioning regimens, and better choice of the UCB unit according to cell dose and HLA typing have led to improved outcomes (2). Various studies have linked individual parameters such as recipient's disease status, cell dose, degree of HLA match, graft type (single vs. double), and anti-thymocyte globulin (ATG) administration with mortality following UCBT (3)(4)(5)(6)(7)(8)(9)(10)(11). However, it remains unclear how these parameters should be best combined to optimize transplantation outcomes and obtain prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the only known treatment for hematopoietic failure is transplantation of bone marrow cells or HSCs [26]. But blood from the placenta and umbilical cord is a rich source of HSCs, too [27]. In the late 1980s, umbilical cord blood was recognized as an important clinical source of HSCs [28,29].…”
Section: Discussionmentioning
confidence: 99%